Pile test method / Azril Aizat Ab Aziz - Ab Aziz, Azril Aizat (Universiti Teknologi MARA, Perak, 2013)
This report briefly describes the methods and planning, equipment and materials involved in the process of piling test. It is produced based on the experience of a five-month practical training in Tunjong Develepment Corporation Sdn. Bhd. and few times to go to the site involved. This report is divided into sections and begins with the company background and the background of the construction project. As a result of observations found pile testing method for this project is quite complicated. In the work of pile testing involves several parties, such as engineers, site supervisors and skilled workers. This report is implemented using several methods of research such as observation, interviews, electronic media and reference materials. In this report, briefly explain the types and equipment used in the process. During the piling test work is done, there are several problems associated with the piling process have been identified and the report ended with some suggestions that felt able to solve problems that have been identified. The results of this report have been able to achieve the objectives of the report of the test pile. Finally, the report will explain in more detail for piling works in practice to the readers.